THE EFFECT OF GROTOP BOSTER ON THE GROWTH AND SURVIVAL RATE OF BAUNG (Hemibagrusnemurus) IN THE RECIRCULATION SYSTEM - Febrino Yudiananda; Usman M. Tang; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT The aim of the study was to determine the optimal doses of boster grotopin increasing the growth and survival of baung fish (Hemibagrusnemurus) in the recirculation system. This research was conducted from Augustuntil October 2019 for 40 days at the Technology LaboratoryAquaculture Faculty of Fisheries and Marine Riau University. Which methodused in this study is an experimental method, usingComplete Random Design (CRD) with 5 levels of treatment and 4 replications.The treatments applied were: P0) 0 g / kg of feed; P1) 15 g / kg of feed; P2) 20 g / kg of feed; P3) 25 g / kg of feed; P4) 30 g / kg of feed. The results showed thatthe addition of a different dose of booster grotopes shows a real effect(P<0.05) to growth in absolute weight (Wm), growth in absolute length(Lm), specific growth rate (LPS), feed efficiency (EP), feed conversion ratio(FCR) and have no significant effect (P>0.05) on the survival rate (SR)baung fish. The best treatment is giving grotop booster 30 g / kg of feed(P4) which produces an absolute weight growth of 3.86 g, long growthabsolute 2.41 cm, specific growth rate 1.62%, feed efficiency 83.55%, feed conversionratio 1.19% and survival 96.67%.Keywords:Doses,BosterGrotop, Recirculation System, Growth,Baung Fish.